The Effect of Pests and Their Co – Infections on Senior High School Students in the Greater Kumasi: A Study of Some Selected Senior High Schools - Adanse, John; Anita Serwaa Agyemang; Sussana Antwi-Boasiako; Grace Efua Owusu Gyasi (Innovations in Science and Technology Vol. 4, 2022)
Pests, insects, and rodents are the common mammals on the planet. These mammals are carriers of over 200 diseases in humans and animals all over the world. They cause extensive damage to a variety of structures. Epidemics and diseases significantly impact a country’s economy because resources that would otherwise be used for developmental projects are diverted to prevent hospitalization and manage outbreaks. Because of rising environmental changes, infected invasive mosquito species have been proven to increase in both local and global borders. The objectives of this chapter were to examine the common occurring pests in the boarding houses which cause the most problem to students; identify pest infestations and determine disease-causing agents of the common occurring pest, and to find out how pests are controlled using chemicals, physical, mechanical method and biological methods, and integrated pest management. A descriptive research design was used to study respondents. A sample size (n) of 227 respondents was used for the study. Simple random sampling, purposive and stratified sampling procedures were used. A questionnaire was used to collect data from respondents. Data were collected and analyzed using the Statistical Package for Social Sciences (SPSS). Data were analyzed using descriptive statistics. It was found that the majority (74.1%) of students had complained of pest and insect-borne diseases and most of these insects and rodents appeared in (43.8%) of bedrooms, (26.4%) in kitchens, and 13.4% in classrooms. This chapter however recommends that the Ghana Education Service should take immediate steps to prevent the spread of pests and insects and this can be done by focusing on preventative measures such as repairing windows or recreation areas, nets and windows, and doors, spraying regularly.